Sampling and evaluation of in-situ studies for 60Co diffusion in bentonite - Beckius, Mikael (My University, 2020)
This study focuses on evaluating the diffusion of 60Co in bentonite clay as part of an in-situ experiment made by SKB at Äspö. This experiment has been running for 20 years, and its purpose is to evaluate the potential of using bentonite clay as backfill material in a final repository for used nuclear fuel. Evaluating the diffusivity is one method of assessing the long-term structural integrity of the bentonite clay. This is done by using 60Co as a radioactive tracer placed in a block of bentonite inside a test parcel designed to mimic the proposed setup of the Swedish KBS-3 final repository model. This specific setup is under adverse conditions where the temperature is higher than the estimated temperature in the final repository. This is done to obtain a comparison with previous studies done under normal conditions. The bentonite around the radioactive source is sampled and crushed before the radioactivity is measured using an HPGe detector with sample changer. The calculated diffusivity is used to evaluate whether the diffusion model used in earlier studies is applicable on this test parcel as well. The results obtained in this study, shown in Table 0.1, supports earlier studies, as the calculated diffusivity fits well into the diffusion model and yields a diffusivity within an order of magnitude from the results obtained in earlier studies for the fast profiles, and in line with earlier results for the slow profiles. Combining this result with the previous studies on the subject show that the bentonite structure appears to be intact, which further supports the idea that bentonite clay is a very promising material for use as backfill material in a final repository.
Keywords: bentonite; diffusion; cobalt; nuclear fuel; final repository; SKB